Adherence to international guidelines for the management of Helicobacter pylori infection among gastroenterologists and gastroenterology fellows in Italy: A Survey of the Italian Federation of Digestive Diseases ‐ FISMAD. Issue 1 (11th November 2021) - Zagari, Rocco Maurizio; Romano, Marco; Frazzoni, Leonardo; Marasco, Giovanni; Dajti, Elton; Arcidiacono, Paolo Giorgio; Armuzzi, Alessandro; Biagi, Federico; Cannizzaro, Renato; Cavestro, Giulia Martina; Ciacci, Carolina; Monica, Fabio; et al.
Abstract: Background: Information on the management of Helicobacter (H . ) pylori infection by gastroenterologists and gastroenterology fellows are scarce. We aimed to assess practice of gastroenterologists and gastroenterology fellows and their adherence to guidelines for diagnosis and treatment of H. pylori infection in Italy. Materials and Methods: All gastroenterologists and gastroenterology fellows attending the National Congress of Digestive Diseases ‐ FISMAD were invited to fill‐in an on‐line questionnaire. The questionnaire included questions on the diagnosis and treatment of H. pylori infection. Results: A total of 279 gastroenterologists and 61 gastroenterology fellows participated to the study. The 13 C‐urea breath test was the most preferred method among gastroenterologists and fellows for the diagnosis of H. pylori infection (40.4% and 57.6%, respectively) and the confirmation of eradication (61.3% and 70%, respectively). Sequential therapy was the most preferred first‐line treatment of H. pylori for both gastroenterologists and gastroenterology fellows (31.8% and 44%, respectively), followed by bismuth quadruple therapy (31% and 27.6%, respectively) and clarithromycin triple therapy (26.8% and 22.4%, respectively). Only 30% of gastroenterologists and 38.5% of fellows used the clarithromycin triple therapy for the recommended duration of 14 days. Bismuth quadruple therapy was the most preferred second‐line therapy for both gastroenterologists and fellows. The majority of gastroenterologists and fellows would prefer an empirical therapy at third line (72.6% and 62.5%, respectively) and a susceptibility‐guided therapy at fourth line (46.7% and 71.4%, respectively). Conclusions: Practices of gastroenterologists and gastroenterology fellows are in line with guidelines' recommendations, apart for the first‐line treatment of H. pylori infection. Targeted educational interventions to improve adherence to guidelines are needed.